Empowering the people: Development of an HIV peer education model for low literacy rural communities in India - Krupp Karl; Rafiq Mirriam; Madhivanan Purnima; Van Rompay Koen KA; Chakrapani Venkatesan; Selvam Durai (BMC, 2008)
Abstract Background Despite ample evidence that HIV has entered the general population, most HIV awareness programs in India continue to neglect rural areas. Low HIV awareness and high stigma, fueled by low literacy, seasonal migration, gender inequity, spatial dispersion, and cultural taboos pose extra challenges to implement much-needed HIV education programs in rural areas. This paper describes a peer education model developed to educate and empower low-literacy communities in the rural district of Perambalur (Tamil Nadu, India). Methods From January to December 2005, six non-governmental organizations (NGO's) with good community rapport collaborated to build and pilot-test an HIV peer education model for rural communities. The program used participatory methods to train 20 NGO field staff (Outreach Workers), 102 women's self-help group (SHG) leaders, and 52 barbers to become peer educators. Cartoon-based educational materials were developed for low-literacy populations to convey simple, comprehensive messages on HIV transmission, prevention, support and care. In addition, street theatre cultural programs highlighted issues related to HIV and stigma in the community. Results The program is estimated to have reached over 30 000 villagers in the district through 2051 interactive HIV awareness programs and one-on-one communication. Outreach workers (OWs) and peer educators distributed approximately 62 000 educational materials and 69 000 condoms, and also referred approximately 2844 people for services including voluntary counselling and testing (VCT), care and support for HIV, and diagnosis and treatment of sexually-transmitted infections (STI). At least 118 individuals were newly diagnosed as persons living with HIV (PLHIV); 129 PLHIV were referred to the Government Hospital for Thoracic Medicine (in Tambaram) for extra medical support. Focus group discussions indicate that the program was well received in the communities, led to improved health awareness, and also provided the peer educators with increased social status. Conclusion Using established networks (such as community-based organizations already working on empowerment of women) and training women's SHG leaders and barbers as peer educators is an effective and culturally appropriate way to disseminate comprehensive information on HIV/AIDS to low-literacy communities. Similar models for reaching and empowering vulnerable populations should be expanded to other rural areas.